FIGURATIVE LANGUAGE IN SELECTED SONGS OF “RED” BY TAYLOR SWIFT - Fatikha, Alya Rizqi; Masykuroh, Qanitah (Universitas Islam Sumatera Utara (UISU), 2022)
This study aims to explore the types and meanings of figurative language in Taylor Swift’s song lyrics. On the surface level, figurative language cannot be translated literally. The study is descriptive qualitative, and the data are in the forms of figurative language taken from eight selected songs in Taylor Swift's album